Essential law for information professionals - Pedley, Paul (Facet Publishing, 2019)
Essential Law for Information Professionals, fourth edition, provides up-to-date and easy-to-follow practical guidance on the law as it affects information management and the principles underlying practice. Using individual cases to illustrate these core principles and contextualise regulations, it cuts through the legalese to provide exactly what's needed in an easily digestible format showing examples of how the law has worked in practice in specific legal cases. The book gives readers the tools to quickly assess legal hazards and identify solutions. Information law is a particularly fast moving area of law. In the eight years that have passed since the best-selling third edition was published, there have been many changes to the legislation and numerous legal cases which have further developed our understanding of the law. The fourth edition fully reflects those changes, which include: a new chapter on library law which covers the legal framework for libraries (concentrating on legislation and soft law relevant to libraries) implementation of the GDPR through the Data Protection Act 2018 a major overhaul of the copyright exceptions, and the 2018 implementation of the Marrakesh Treaty the Re-Use of Public Sector Information Regulations 2015 and the implications of the 2018 proposals for a new re-use directive extension of the public lending right scheme to e-books CILIP's ethical framework. Readership: Essential Law for Information Professionals is an essential guide for anyone working in the information professions. It is also the ideal legal textbook for students of information studies and librarianship.